2020
DOI: 10.1634/theoncologist.2019-0898
|View full text |Cite
|
Sign up to set email alerts
|

EMA Recommendation for the Pediatric Indications of Plerixafor (Mozobil) to Enhance Mobilization of Hematopoietic Stem Cells for Collection and Subsequent Autologous Transplantation in Children with Lymphoma or Malignant Solid Tumors

Abstract: On March 28, 2019, the Committee for Medicinal Products for Human Use adopted a positive opinion recommending the marketing authorization for the medicinal product plerixafor. The marketing authorization holder for this medicinal product is Genzyme Europe B.Th. The adoption was for an extension of the existing adult indication in combination with granulocyte colony‐stimulating factor (G‐CSF) to pediatric patients (aged 1 year to <18 years) to enhance mobilization of hematopoietic stem cells to the peripheral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…In the phase I part of their study (n = 27), Morland et al determined the dose of plerixafor in children to be 240 μg/kg which was the dose received by majority of patients in our cohort. Previous studies have reported a median 3.2 to 13-fold 3,7,21,22 increase in PB CD34+ count following plerixafor administration, we observed a median 4-fold increase in PB CD34+ counts using this agent. In phase II study from Europe, 80% of children who received plerixafor upfront with SM achieved doubling of PB CD34+ vs 28.6% of those who received SM alone.…”
Section: Discussionsupporting
confidence: 59%
“…In the phase I part of their study (n = 27), Morland et al determined the dose of plerixafor in children to be 240 μg/kg which was the dose received by majority of patients in our cohort. Previous studies have reported a median 3.2 to 13-fold 3,7,21,22 increase in PB CD34+ count following plerixafor administration, we observed a median 4-fold increase in PB CD34+ counts using this agent. In phase II study from Europe, 80% of children who received plerixafor upfront with SM achieved doubling of PB CD34+ vs 28.6% of those who received SM alone.…”
Section: Discussionsupporting
confidence: 59%
“…Even though G‐CSF remains the standard for PBSC mobilization, alternative mobilization policy, such as twice daily G‐CSF schedule (split dose) or the use of molecules like AMD3100, might be considered for donors who turn out to be poor mobilizers. Plerixafor (AMD3100) was approved in adult patients in 2009 by the European Medicines Agency for use in combination with G‐CSF, to enhance the mobilization of hematopoietic stem cells to peripheral blood, and recently has received a positive opinion by the Committee for Medicinal Products for Human Use of the European Medicines Agency for its use in combination with G‐CSF in pediatric patients to enhance mobilization of hematopoietic stem cells for collection and subsequent autologous transplantation in children with lymphoma or solid malignant tumors 37,38 …”
Section: Discussionmentioning
confidence: 99%
“…Considering the pharmacokinetic and pharmacodynamic differences between the pediatric and adult population, direct extrapolation of adult data is not possible. To address these issues, a two‐phase study (DFI12860) was designed, containing a dose‐ranging part (phase I) followed by a small randomized comparative study (phase II) to support the extension of the indication of plerixafor to pediatric patients 38 . It is worth mentioning the association that was found between exposure to the drug, with age and weight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations